2022
DOI: 10.1002/cbdv.202200538
|View full text |Cite
|
Sign up to set email alerts
|

Cladosporioles A and B, Two New Indole Derivatives from the Deep‐Sea‐Derived Fungus Cladosporium cladosporioides 170056

Abstract: Two new (cladosporioles A and B, 1 and 2) and fourteen known (3–16) compounds were isolated from the deep‐sea‐derived fungus Cladosporium cladosporioides 170056. The relative structures of the new compounds were elucidated mainly by detailed analysis of their NMR and HR‐ESI‐MS spectroscopic data. Their absolute configurations were determined by comparison of the experimental and calculated electronic circular dichroism (ECD) spectra. All isolates were tested for antimicrobial activity against Vibrio parahaemol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In summary, three new aminated fusaric acid derivatives, hepialiamides A-C (1-3), and one novel hybrid polyketide, hepialide (4), together with 18 known miscellaneous compounds (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), were isolated from the cultures of the deep-sea-derived fungus Samsoniella hepiali W7 with the aid of GNPS molecular networking. Hepialiamides A-C feature a glycine/alanine unit embedded in the fusaric acid backbone, representing the third examples of naturally occurring fusaric amides, while hepialide features an uncommon isopropenylated pyrrolidone moiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, three new aminated fusaric acid derivatives, hepialiamides A-C (1-3), and one novel hybrid polyketide, hepialide (4), together with 18 known miscellaneous compounds (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), were isolated from the cultures of the deep-sea-derived fungus Samsoniella hepiali W7 with the aid of GNPS molecular networking. Hepialiamides A-C feature a glycine/alanine unit embedded in the fusaric acid backbone, representing the third examples of naturally occurring fusaric amides, while hepialide features an uncommon isopropenylated pyrrolidone moiety.…”
Section: Discussionmentioning
confidence: 99%
“…As part of our ongoing exploration of structurally novel and bioactive secondary metabolites from marine microbes [21][22][23][24], we performed a systematic investigation, aided by a GNPS molecular networking approach, on the crude extract of the culture of fungus Samsoniella epialid W7, isolated from the sulfide at a depth of 3073 m in the South Atlantic. Prior to isolation, the GNPS network of the extract revealed a big molecular cluster within which none of the nodes were identified by the internal compound library (Figure 1), indicating a certain possibility of new compounds to be found among these metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…A SAR study of the new analogues indicated key structural requirements for reversal of P-glycoprotein efflux mediated doxorubicin resistance in a HTCL. 186 Cladosporium strains derived from deep-sea sediment were the sources of indole derivatives 514 and 515 , 187 sulfur and peroxy bridged macrolide 516 and iodinated dimeric naphtho-γ-pyrone 517 (ref. 188) and oxygenated fatty acids, seco -patulolides 518 – 520 .…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%